Approximation Methods in Variational Problems - Amaral, Henrique Mariano do; Abreu , Ivanildo Silva; Teixeira, Cristovam Filho Dervalmar Rodrigues; Junior, Elder Abreu; Silva, Rildenir Ribeiro; Aragão, Alan Jefferson Lima; Reis, Vankys Ferreira; Pereira, Karllos Alexandre Sousa; Rodrigues, Marcus Vinicius Viegas; Veras, Danilo Furtado (Seven Editora, 2024)
This research material suggests the exploration of approaches to deal with variational problems through approximation techniques. In mathematical contexts, variational problems involve optimization of functions, and approximation methods seek to find approximate solutions to these problems. These approaches can be essential in situations where finding an exact solution is challenging or impractical, allowing for the effective analysis and resolution of complex issues through approximation techniques. DOI:https://doi.org/10.56238/sevened2023.006-150